Studying food entrainment: Models, methods, and musings - Trzeciak, Jacqueline R.; Steele, Andrew D. (Frontiers in Nutrition, 2022)
The ability to tell time relative to predictable feeding opportunities has a long history of research, going back more than one hundred years with behavioral observations of honeybees and rats. Animals that have access to food at a particular time of day exhibit “food anticipatory activity” (FAA), which is a preprandial increase in activity and arousal thought to be driven by food entrained circadian oscillator(s). However, the mechanisms behind adaptation of behavior to timed feeding continue to elude our grasp. Methods used to study circadian entrainment by food vary depending on the model system and the laboratory conducting the experiments. Most studies have relied on rodent model systems due to neuroanatomical tools and genetic tractability, but even among studies of laboratory mice, methods vary considerably. A lack of consistency within the field in experimental design, reporting, and definition of food entrainment, or even FAA, makes it difficult to compare results across studies or even within the same mutant mouse strain, hindering interpretation of replication studies. Here we examine the conditions used to study food as a time cue and make recommendations for study design and reporting.